Project-based learning for engineer’s creativity fostering - Titova, Olena; Тітова, Олена Анатоліївна; Титова, Елена Анатольевна (My University, 2018)
Engineering schools all over the world are facing a number of key issues these days. Fostering student’s creativity is one of the most pressing as creativity is among highly desirable skills of nowadays. Since project-based learning is rightly considered to be one of the leading methods in engineering education it was applied for the current research. Projects are not an innovative approach at Ukrainian high school. Though, the fact that it had lost its efficiency became a reason for searching after new ways. Application of Engineering Design Process revealed a whole number of improvements. High level of student’s motivation and engagement as well as an independent cognitive activity and tangible creative results, which could be included in student’s portfolios, comprised the strong sides. The weakness of the method is the lack of knowledge and confidence among engineering teachers who have difficulties both with proper application and evaluation practices. So the further study might be devoted to the development of the easily transferable project-based models as well as mechanisms of funding and supporting such activities at Ukrainian engineering schools.
Keywords: engineering education; engineer’s creative potential; project-based learning